Pendampingan Dan Penerapan Branding Produk Sebagai Strategi Pemasaran UMKM “Rempeyek Mak Sri” - Ismiatul Ilmiah; Nanik Hariyana (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
UMKM plays a significant part in the economy of the nation. The rapid development of technology in this era led to the marketing of products using the internet. Product branding is crucial in product marketing in order to grab the public's attention and pique their interest in purchasing a UMKM product. Rempeyek Mak Sri is one of the UMKM that engages in branding by participating in the socialization of "strategy adaptation in the globalization Era," developing logos and labels, as well as social media accounts and marketplaces to assist marketing.